Police experiences of bystander assistance in pre-hospital care of road traffic accident victims in Abuja, Nigeria: a cross-sectional study - Kehinde O Ogunyemi, MBBS; Chinmayee Venkatraman, BS; Chenchita Malolan, MPH; Oluwole Olaomi, FWACS; Fiemu E Nwariaku, FACS (Elsevier, 2021)
Background: Globally, most deaths from road traffic accidents (RTA) occur before the injured person reaches hospital. This mortality burden is disproportionately higher in Africa, with Nigeria having a mortality burden from RTA, at 21·4 per 100 000 people, that is six-times higher than that in high-income countries such as Norway (3·1 per 100 000 people). Bystander first aid is associated with improved survival of trauma victims and Norway has a high rate of bystander first aid to RTA victims (89%); however, data on bystander first aid for RTA victims are lacking in Nigeria. The objectives of this study were to: (1) determine the bystander assistance rate to RTA victims; (2) assess the prevalence of bystander first aid to RTA victims; and (3) evaluate bystander non-helping behaviours to RTA victims. Methods: This was a cross-sectional study that used observer-report data collected from police officers at 31 police stations in Abuja, Nigeria. A stratified randomised sample of 428 police officers were interviewed using a structured electronic pre-tested questionnaire for data collection. The questionnaires were self-administered. We collected data on sociodemographic characteristics of police officers and they were asked to report information on bystander assistance, first aid, and non-helping behaviours during their last pre-hospital care encounters with RTA victims in Abuja. To calculate the bystander assistance rate and the prevalence of first aid, we defined bystander assistance as any activities such as calling the police or ambulance service and first aid to save the lives of RTA victims. First aid was defined as basic care such as chest compression or wound dressing given to stabilise RTA victims either at the scene of injury or during transportation to the hospital. Descriptive statistics were summarised using STATA v. 14.0. Findings: Between Nov 21, 2018, and Dec 8, 2018, we included data from 281 police officers who had ever provided pre-hospital care to RTA victims in Abuja. The bystander assistance rate to RTA victims was 93·2% (n=262). Provision of first aid and calling the police or ambulance service were the most common form of bystander assistance (31·3% [n=82] and 28·2% [74], respectively). Other bystander assistance included provision of safety for RTA victims or first-aiders (20·2% [53]), and search and rescue for life and property near the accident scene (19·8%% [52]). The rate of bystander first aid to RTA victims was 29·2% (82). Of the bystander non-helping behaviours reported (6·8% [19]), gazing or just looking accounted for the most (68% [13]), followed by stealing victims' property (21% [4]). Interpretation: The rate of bystander first aid to RTA victims in Nigeria is significantly lower than those in high-income countries such as Norway and is likely to contribute to increased RTA mortality. Our findings highlight the need to increase community access to first aid trainings and behaviour-change interventions to improve RTA victims' health outcomes. Funding: NIH and Fogarty International Center Training Grant for Partnerships to Develop Injury Research Capacities in Sub Saharan Africa (5D43TW010463-03) by Office of Global Health, University of Texas Southwestern Medical Center, USA.